2012
DOI: 10.1002/jbm.b.31983
|View full text |Cite
|
Sign up to set email alerts
|

Influence of carboxymethyl chitin on stability and biocompatibility of 3D nanohydroxyapatite/gelatin/carboxymethyl chitin composite for bone tissue engineering

Abstract: A novel three-dimensional (3D) scaffold has been developed from the unique combination of nanohydroxyapatite/gelatin/carboxymethyl chitin (n-HA/gel/CMC) for bone tissue engineering by using the solvent-casting method combined with vapor-phase crosslinking and freeze-drying. The surface morphology and physiochemical properties of the scaffold were investigated by dissolvability test, infrared absorption spectra (IR), X-ray diffraction (XRD), transmission electron microscope (TEM), scanning electron microscope (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 36 publications
(41 reference statements)
1
27
0
Order By: Relevance
“…32 In addition, the incorporation of HA can improve the cytocompatibility of the bone cement as evidenced by the MTT assay, and the cell viability results showed that the composite bone cement was non-toxic ( Figure 6b). HA is known to be a good substrate for attachment of extracellular matrix (ECM) adhesion proteins 33 , which could promote cellular attachment.…”
Section: Discussionmentioning
confidence: 97%
“…32 In addition, the incorporation of HA can improve the cytocompatibility of the bone cement as evidenced by the MTT assay, and the cell viability results showed that the composite bone cement was non-toxic ( Figure 6b). HA is known to be a good substrate for attachment of extracellular matrix (ECM) adhesion proteins 33 , which could promote cellular attachment.…”
Section: Discussionmentioning
confidence: 97%
“…Microarchitectural parameters including, bone volume fraction (BV/TV), trabecular thickness (Tb.Th), trabecular separation (Tb.Sp), trabecular number (Tb.N) and structure model index (SMI) were quantified as described before [33,34] Loading of MSC with 3D Scaffold at Fractured Site To study the therapeutic effect of cont MSC and Ovx MSC in equal number with 3D scaffold at fractured site in female rats was evaluated. A 3-D nano-hydroxyapatite/gelatin/ carboxymethyl chitin (n-HA/gel/CMC) scaffold constructs were prepared by solvent casting method combined with glutaraldehyde vapour crosslinking and freeze drying method as described before [35,36]. The scaffolds were removed from the sterile patches and wetted with blood that oozed out from the incision during surgery.…”
Section: Micro-computed Tomography (μCt)mentioning
confidence: 99%
“…The n-HA/gel/CMC scaffold constructs were prepared by solvent casting method combined with glutaraldehyde vapor crosslinking and freeze drying method as mentioned in our previous report [34]. In brief, monobasic calcium phosphate is reacted with a calcium hydroxide solution.…”
Section: Methodsmentioning
confidence: 99%
“…It would be more effective; if along with the above tailorable hybrid properties the material is carvable and/or amenable to contouring for optimal adaptation to the various shapes of bone defects without failure and or fracture [3133]. We have developed such biomaterial as a self-organized n-HA/gel/CMC scaffold construct and have been successfully tested concerning its physicochemical, morphological, mechanical, hemocompatible and biocompatible properties to prove the influence of acidic derivative of natural polymer used in functionalization (due to presence of both carboxyl and amino groups) of the composite material [34]. Herein, we test the in vivo feasibility of the n-HA/gel/CMC scaffold construct to act as a process-directing agent to promote mineralized tissue formation for the treatment of bone defects.…”
Section: Introductionmentioning
confidence: 99%